«КƏСІБИ ОҚЫТУ» БАКАЛАВРЫН ДАЯРЛАУДАҒЫ ТЕХНОЛОГИЯ МƏСЕЛЕСІ. - Шарзадин, А. М. (Journal of Educational Sciences, 2016)
Данная статья «Проблемы технологий в подготовке бакалавра «Профессионального обучения» является одной из главных тем учебного процесса вуза. В статье автор рассматривает роль и значение технологической подготовки бакалавра «Профессионального обучения», приводит межпредметную связь ряда дисциплин даннойспециальности.The Scientific article "Use technology in system of preparing the bachelor of the professional education" is dedicated to one of actual that society. In given work author considers the types technology, him is made extensive analysis main technology, which are used in scholastic process of the high school, also reveals the role and importance technology in preparing the bachelor of the professional education.